Sustainable Development for Canada's Arctic and Subarctic Communities: A Backcasting Approach to Churchill, Manitoba - Newton, Steven Timothy; Fast, Helen; Henley, Thomas (ARCTIC, 2002)
Backcasting has been used to evaluate sustainable development in several communities in Canada, Europe, and the United States, but no research has applied it to a remote northern community. This first such effort, which took place in Churchill, Manitoba, evaluated the environmental, social, and economic aspects of a small Subarctic community. As part of the backcasting approach, a community survey identified local issues and concerns, such as tundra vehicle damage, alcohol abuse, and the future economic viability of the Hudson Bay Port Company. Community residents also identified potential growth areas, including the establishment of Nunavut and increased tourism opportunities. The application of the backcasting approach in Canada's northern regions will have benefits for research and management by identifying local issues and building strategies for sustainable development. L'analyse rétrospective a été utilisée pour évaluer le développement durable dans diverses communautés du Canada, d'Europe et des États-Unis, mais aucun travail de recherche ne l'a appliquée à une communauté isolée du Grand Nord. Cette première tentative du genre, qui s'est déroulée à Churchill, au Manitoba, a évalué les facettes environnementales, sociales et économiques d'une petite collectivité subarctique. Dans le cadre de la méthode de l'analyse rétrospective, un sondage auprès de la communauté a permis d'identifier les préoccupations et enjeux locaux, tels que les dommages à la toundra causés par les véhicules, l'abus d'alcool et la future viabilité économique de la Compagnie du port de la baie d'Hudson. Les résidents de la communauté ont également identifié des zones de croissance potentielle, y compris l'établissement du Nunavut et des ouvertures accrues sur le plan touristique. L'application de la technique de l'analyse rétrospective dans les régions nordiques du Canada sera bénéfique pour la recherche et la gestion en identifiant les enjeux locaux et en édifiant des stratégies visant le développement durable.